The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1007/s10593-008-0006-8
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 2-amino-4H-3,1-benzoxazines and 2-amino-4H-3,1-benzothiazines by the rearrangement of o-cyclopropylphenylureas and o-cyclopropylphenylthioureas

Abstract: Syntheses are reported for 2-cyclopropylphenylureas and 2-cyclopropylphenylthioureas and the behavior of these compounds was studied under conditions for the acid-catalyzed opening of the cyclopropyl ring. Upon the action of concentrated sulfuric acid or trifluoroacetic acid, these ureas and thioureas can undergo rearrangement to the corresponding 3,1-benzoxazines and 3,1-benzothiazines.Functionally-substituted cyclopropanes, which have now become readily available, are finding increasing use as starting compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 19 publications
0
0
1
Order By: Relevance
“…It can be confirmed that solvent conditions play an important role in affecting the tautomeric equilibrium. This result is slightly different from that obtained by Shabarov and coworkers [22]. Interestingly, another type of cyclization product 5 (Scheme 1), which can be formed through an intramolecular N-nucleophilic attack rather than S-nucleophilic attack, was not observed.…”
Section: Resultscontrasting
confidence: 84%
“…It can be confirmed that solvent conditions play an important role in affecting the tautomeric equilibrium. This result is slightly different from that obtained by Shabarov and coworkers [22]. Interestingly, another type of cyclization product 5 (Scheme 1), which can be formed through an intramolecular N-nucleophilic attack rather than S-nucleophilic attack, was not observed.…”
Section: Resultscontrasting
confidence: 84%